Why Do Canadian Firms Cross-list? The Flip Side of the Issue - Charitou, Andreas; Louca, Christodoulos (My University, 2017)
We investigate the relation between managerial incentives and the decision to cross-list by comparing Canadian firms cross-listed on US stock exchanges to industry- and size-matched control firms. After controlling for firm and ownership structure characteristics, we find a positive association between substantial holdings of vested options held by CEOs prior to cross-listing and the decision to cross-list. Further, firms managed by CEOs with substantial holdings of vested options exhibit positive announcement returns and negative post-announcement long-run returns. CEOs of cross-listed firms seem to take advantage of the aforementioned market behaviour, because they abnormally exercise vested options and sell the proceeds during the year of listing only when their firms underperform during the subsequent year. In addition, there is a positive relation between substantial holdings of vested options and discretionary accruals during the year of listing, consistent with the view that CEOs manage earnings to keep stock prices at high levels. Overall, these results have significant implications for the cross-listing literature, suggesting an association between cross-listing and CEO incentives to maximize CEO private benefits.
Keywords: CEO compensation; Cross-listing; Vested options